Perilaku Kepala Desa Sebagai Pengelola Dana Desa - Hendrarto Widodo; Alwan Sri Kustono; Whedy Prasetiyo (Jurusan Akuntansi Fakultas Ekonomi Universitas Islam 45, 2019)
This research aimed to determine the behavior of the village head in managing village funds. The behavior in question is the behavior of the village head in participatory planning, the behavior of the village head in the transparency of village fund management and the behavior of the village head in the accountability of village fund management. This research was conducted in the Kemiren Customary village of Glagah sub-district, Banyuwangi Regency using descriptive qualitative methods. The results showed that participatory planning, transparency and accountability of village fund management conducted by the village head were still not at the ideal level.